Intellectual Innovation in The Manufacturing Enterprise - Case Study - Aleksandra KUMOR-SULERZ; Dagmara MICHTA (Communications of International Proceedings, 2022)
The article presents the innovation assessment of company from the fertilizer and chemical industry as an example. The study has shown that it has a high level of intellectual innovation and a medium level of technological innovation. The intention of this article is a representation of the state of technological development in a manufacturing company using the original method for diagnosing the innovation status of a company, which allows the technology used by a company to be assessed against the Technology Readiness Levels (TRL) classification. The study provides information on the development and use of new technologies in the company as well as on the company’s experience with product and technology development. This information provides insight into the company’s potential research and development opportunities, which is helpful in formulating directions for development.
Keywords: Innovation enterprise; Technology Readiness Level (TRL)